A study on the spatial distribution of life expectancy and its air pollution factors in China based on geographically weighted regression - Hu, Ke; Zhang, Xing; Yang, Xingjin; Yu, Mingyang (Frontiers in Public Health, 2025)
BackgroundLife expectancy in China has demonstrated a consistent upward trend, yet significant disparities persist across provinces. Addressing these regional imbalances necessitates a comprehensive investigation into the determinants of life expectancy. Previous research has largely overlooked the critical role of spatial heterogeneity, which is essential for understanding the underlying mechanisms driving these disparities. By incorporating spatial analysis, this study aims to identify and address the factors contributing to the uneven distribution of life expectancy across China, thereby providing a more nuanced understanding of regional health inequalities.MethodsTherefore, this study investigated the spatial distribution characteristics and patterns of life expectancy across 31 provinces in China in 2020 by conducting descriptive and spatial autocorrelation analyses, utilizing life expectancy data alongside key air pollution indicators (PM2.5, SO2, NO2, and PM10). To address spatial heterogeneity, the geographically weighted regression (GWR) model was applied to assess the regional variations in the impact of air pollutants on life expectancy. This approach allows for the incorporation of geographic coordinates into the regression coefficients, capturing localized effects and providing a more nuanced understanding of the relationship between air pollution and life expectancy across different regions.ResultsThe findings revealed that in 2020, life expectancy in China exhibited a distinct east-to-west decreasing trend, demonstrating significant spatial autocorrelation that was predominantly characterized by two aggregation patterns: high-high and low-low clusters. The analysis demonstrated that air pollutants, including SO2, NO2, and PM10, exerted significant influences on life expectancy, albeit with regional variations. Specifically, SO2 exhibited a more pronounced negative impact on life expectancy in southern cities, while NO2 demonstrated a stronger effect in northwestern regions. Notably, PM10 showed a significant influence limited to Yunnan Province, highlighting the spatial heterogeneity in the relationship between air pollution and life expectancy across China.ConclusionThese findings highlight the imperative for local governments to develop and implement region-specific air pollution control measures, taking into account the unique environmental and socio-economic conditions of their respective areas.